Implementation of Art Therapy Through the Creative Process of Creating Paintings to Reduce the Stress Levels of Students - Kadek Jaya Sumanggala; Pujiyanto Pujiyanto; Robby Hidayat (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Education aims to shape students to become human beings who are intelligent in thinking, morals, and able to fully realize their full potential. The higher the level of education will be in line with the increasingly heavy learning load. High learning loads and high social demands can also affect students' stress levels. So, it is not uncommon for students as students to experience a lot of despair which leads to suicide. These problems can be overcome by applying art therapy through a creative process. This study aims to apply art therapy through a creative process to reduce student stress levels. This study used mixed methods with a one-group design through tests (pre-test & post-test) and painting the results before and after the intervention. The research subjects were selected by purposive sampling technique by taking the subject of a high-stress level 4 people consisting of two men and two women. The data analysis techniques used in this study include a) data collection, b) data reduction, c) data presentation, and d) draw conclusions. Data collection instruments used in one group of research subjects consisted of pre-test & post-test before and after intervention using the Anxiety Stress Scales (DASS-42), observation, interviews, and documentation. The results of the study show that art therapy through a creative process can reduce student stress. This is proven from a comparison of the paintings before and after the intervention through art analysis. The results of the paintings show that the images of academic pressure and social pressure on students, after the intervention, there is a significant difference between one painting and another. In addition, the results of interviews conducted with the four research subjects felt more confident and self-controlled. The total score of the four subjects before the intervention was 123 with details of 36 (physical), 42 (emotional), and 45 (behavior), then after the intervention, the total score was 87 with details of 25 (physical), 32 (emotional), and 30 (behavior). So, this proves that art therapy is effective in reducing stress levels in college.